Association of Concentric Left Ventricular Hypertrophy With Subsequent Change in Left Ventricular End-Diastolic Volume: The Dallas Heart Study. (August 2017) - Garg, Sonia; de Lemos, James A.; Matulevicius, Susan A.; Ayers, Colby; Pandey, Ambarish; Neeland, Ian J.; Berry, Jarett D.; McColl, Roderick; Maroules, Christopher; Peshock, Ronald M.; Drazner, Mark H.
Abstract : Background: In the conventional paradigm of the progression of left ventricular hypertrophy, a thick-walled left ventricle (LV) ultimately transitions to a dilated cardiomyopathy. There are scant data in humans demonstrating whether this transition occurs commonly without an interval myocardial infarction. Methods and Results: Participants (n=1282) from the Dallas Heart Study underwent serial cardiac magnetic resonance ≈7 years apart. Those with interval cardiovascular events and a dilated LV (increased LV end-diastolic volume [EDV] indexed to body surface area) at baseline were excluded. Multivariable linear regression models tested the association of concentric hypertrophy (increased LV mass and LV mass/volume 0.67 ) with change in LVEDV. The study cohort had a median age of 44 years, 57% women, 43% black, and 11% (n=142) baseline concentric hypertrophy. The change in LVEDV in those with versus without concentric hypertrophy was 1 mL (−9 to 12) versus −2 mL (−11 to 7), respectively, P <0.01. In multivariable linear regression models, concentric hypertrophy was associated with larger follow-up LVEDV ( P ⩽0.01). The progression to a dilated LV was uncommon (2%, n=25). Conclusions: In the absence of interval myocardial infarction, concentric hypertrophy was associated with a small, but significantly greater, increase in LVEDV after 7-year follow-up. However, the degree of LV enlargement was minimal, and few participants developed a dilated LV. These data suggest that if concentric hypertrophy does progress to a dilated cardiomyopathy, such a transition would occur over a much longer timeframe (eg, decades) and may be less common than previously thought. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00344903. Abstract : Supplemental Digital Content is available in the text.